PERSEPSI, SIKAP DAN PERILAKU PARA GURU DI BALI TERHADAP KONSERVASI SATWA LIAR - Kaler Surata, Sang Putu (Bumi Lestari; Vol 4 No 2, 2012)
This paper describes how the attitude and behavior of Balinese teachers toward the natural world and its conservation, mainly wild animal. For this purpose, we conducted survey using a combination of open and closed-ended questions of high and middle school teachers at eight regency/city in Bali. There were three main topics in this survey, i.e. attitude toward wild animal, attitude about management of wild animal and behavior toward wild animal. The results was indicated that Balinese teacher appreciation toward wild animal very high in natural-aesthetic, habitat-ecologistic, and consumption but lacking scientistic perspective. Concerning of wildlife conservation, we found a majority of the teachers supported development projects if relatively significant human benefits were provided, and regardless of its impact on the rarely or endangered animals. The behavior of more than one-half Balinese teachers showed strong affection for particularly favored wild animal, especially various species of birds. On the other hand, around three-fourth of the teachers did not participate in activity of environmental conservation since last two years.
Keywords: attitude, behavior, endangered and environment